1996
DOI: 10.1080/01652176.1996.9694613
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ciprofloxacin in sheep after single intravenous or intramuscular administration

Abstract: SUMMARYThe disposition and urinary excretion of ciprofloxacin (CIP) following intravenous (IV) or intramuscular (IM) administration of 7.5 mg/kg body weight in sheep (n = 5) was studied. The intravenous plasma concentration The urinary data showed a significant decrease in the elimination rate constant of CIP when CIP was administered intramuscularly. The other parameters calculated did not display differences between the two routes of administration. The results obtained suggest that when CIP was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…after intravenous administration, serum ciprofloxacin concentration (mean± SE) versus time data in dogs were best fitted to a two-compartment open model. This is comparable with the results of other studies in chicken (Anadoan et al, 2001), and in rabbits (Sahar and Eman, 2014), sheep (Munoz et al, 1996), goats (Raina et al, 1994), pre-ruminant calves (Nouws et al, 1988) and dogs (Abadia et al, 1995). Based on the compartmental model of analysis, distribution kinetic parameters, namely-distribution rate constant (α;3.46 ± 0.13 h ) suggested that rapid distribution of the drug from blood to tissues and body fluids.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…after intravenous administration, serum ciprofloxacin concentration (mean± SE) versus time data in dogs were best fitted to a two-compartment open model. This is comparable with the results of other studies in chicken (Anadoan et al, 2001), and in rabbits (Sahar and Eman, 2014), sheep (Munoz et al, 1996), goats (Raina et al, 1994), pre-ruminant calves (Nouws et al, 1988) and dogs (Abadia et al, 1995). Based on the compartmental model of analysis, distribution kinetic parameters, namely-distribution rate constant (α;3.46 ± 0.13 h ) suggested that rapid distribution of the drug from blood to tissues and body fluids.…”
Section: Discussionsupporting
confidence: 82%
“…In current study Distribution half-life of ciprofloxacin in dogs (0.20 ± 0.0 5) hours was longer than that in sheep (2.38 min) (Munoz et al, 1996), and pigs and pre-ruminant calves (Nouws et al, 1988), and in calves (7.8 min) suggesting thereby that the disposition kinetic behavior of drugs differ among different species of animals.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…injection. The plasma concentration time profile was adequately described by a two-compartment open model (based on the Akaike, r 2 and positive and negative residuals) following intravenous administration, as has already been reported by Munoz et al (1996). The correlation coefficient (r 2 ) of the fit of the curve was 0.98.…”
Section: Resultsmentioning
confidence: 98%
“…Pharmacokinetic behavior of ciprofloxacin was well characterized in calves, rabbits, ponies, sheep, rats, cow calves and buffalo calves (Nouws et al, 1988;Dowling et al, 1995;Munoz et al, 1996;Kumar et al, 1997;Zhu et al, 1999a,b;Raina et al, 2000;Jayakumar et al, 2000). Intestine is considered an important pathway in elimination of fluoroquinolones including ciprofloxacin .…”
Section: Introductionmentioning
confidence: 99%